2019
DOI: 10.1002/pat.4647
|View full text |Cite
|
Sign up to set email alerts
|

Induced birefringence of rubbed and stretched polyvinyl alcohol foils as alignment layers for nematic molecules

Abstract: Some optical properties of poly (vinyl alcohol) (PVA) films are investigated prior and after the rubbing and stretching of the samples. Birefringence of the prepared foils is enhanced as their stretching degree and rubbing become larger. These processing factors are also affecting the values of the ordinary and extraordinary refractive indices. The induced anisotropy in PVA foils is evidenced in the morphological characteristics observed by optical microscopy. The spreading and adhesion behaviors of a nematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…[ 31, 32 ] Other important contributions on this subject were made by Dorohoi and collaborators. [ 33‐41 ] The authors developed a method for evaluation of the birefringence and its dispersion, based on the light polarization state of the stretched polymer films, and analyzed the dichroism of the pure and dye‐containing polymers. Their studies showed that transparent polymer films represent adequate media for the orientation of certain spectrally active molecules, and their dichroism allows establishing the direction of the electronic transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 31, 32 ] Other important contributions on this subject were made by Dorohoi and collaborators. [ 33‐41 ] The authors developed a method for evaluation of the birefringence and its dispersion, based on the light polarization state of the stretched polymer films, and analyzed the dichroism of the pure and dye‐containing polymers. Their studies showed that transparent polymer films represent adequate media for the orientation of certain spectrally active molecules, and their dichroism allows establishing the direction of the electronic transition.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanically drawn PVOH films are usually uniax materials, [ 35 ] while their anisotropy increases during the stretching process, which is performed under mild heating. [ 38, 42 ]…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 shows that although the initial fluorescence intensity of all membranes was different, upon 180 min of production, they all exhibited a similar value. This fluorescence quenching, previously described by Nechifor et al [34], is due to the chemical interaction between the entrapped species (nanofluids and [Tmi][Trif]) and the crosslinker (GA), which results in an increase in the non-radiative decay mechanism.…”
Section: Nanofluids' Immobilization On Pva Membranesmentioning
confidence: 81%
“…The entrapment of Cdots within PVA ( Figure 7) was previously accomplished using Cdots with different functionalization, which resulted in refractive index tuning [30], shape-memory effects [31,32], and charge-trapping composites [33]. Indeed, and even though crosslinking of PVA is necessary to increase water resistance, this process has a substantial effect on the optical properties of the entrapped material [34]. (Figure 8).…”
Section: Nanofluids' Immobilization On Pva Membranesmentioning
confidence: 99%
See 1 more Smart Citation